A Nonlinear Prediction Approach to the Blind Separation of Convolutive Mixtures. (24th September 2006) - Suyama Suyama, Ricardo Ricardo; Duarte Duarte, Leonardo Tomazeli Leonardo Tomazeli; Ferrari Ferrari, Rafael Rafael; Rangel Rangel, Leandro Elias Paiva Leandro Elias Paiva; Attux Attux, Romis Ribeiro de Faissol Romis Ribeiro de Faissol; Cavalcante Cavalcante, Charles Casimiro Charles Casimiro; Von Zuben Von Zuben, Fernando José Fernando José; Romano Romano, João Marcos Travassos João Marcos Travassos
Abstract : We propose a method for source separation of convolutive mixture based on nonlinear prediction-error filters. This approach converts the original problem into an instantaneous mixture problem, which can be solved by any of the several existing methods in the literature. We employ fuzzy filters to implement the prediction-error filter, and the efficacy of the proposed method is illustrated by some examples.